2008
DOI: 10.1590/s1516-35982008001200014
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da inclusão de farelo do resíduo de manga no desempenho de frangos de corte de 1 a 42 dias

Abstract: Um experimento foi conduzido com o objetivo de avaliar a utilização de farelo do resíduo de manga (FRM) (Mangifera indica L., var. Ubá) em rações para frangos de corte de 1 a 42 dias de idade. Utilizaram-se 600 pintos machos, Ross, distribuídos em delineamento inteiramente casualizado, com cinco tratamentos, cada um com seis repetições de 20 aves por unidade experimental. Os tratamentos consistiram da inclusão de 0,0; 2,5; 5,0; 7,5 ou 10,0% de farelo do resíduo de manga em dietas à base de milho e farelo de so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
2
3
0
9
Order By: Relevance
“…MARTIN et al (2012) reported contents of total phenolic compounds of 229.2 mg GAE g -1 (dry sample) in grape marc 'Pinot Noir', and this value was higher than the reported in this research (Table 1). In other reseaches, contents of total phenolics of 58mg GAE g -1 in mango bagasse 'Uba' (VIEIRA et al, 2008) and 79.36mg GAE g -1 in peanut skin (CAMARGO et al, 2012) have also been reported, and they are close to the values reported in this research. In terms of dry extract, THIMOTHE et al (2007) reported in grape marc 'Pinot Noir' a total phenolic compounds of 618.0 mg GAE g -1 in ethanolic dry extract, a result close to that observed in this research.…”
Section: Resultssupporting
confidence: 88%
“…MARTIN et al (2012) reported contents of total phenolic compounds of 229.2 mg GAE g -1 (dry sample) in grape marc 'Pinot Noir', and this value was higher than the reported in this research (Table 1). In other reseaches, contents of total phenolics of 58mg GAE g -1 in mango bagasse 'Uba' (VIEIRA et al, 2008) and 79.36mg GAE g -1 in peanut skin (CAMARGO et al, 2012) have also been reported, and they are close to the values reported in this research. In terms of dry extract, THIMOTHE et al (2007) reported in grape marc 'Pinot Noir' a total phenolic compounds of 618.0 mg GAE g -1 in ethanolic dry extract, a result close to that observed in this research.…”
Section: Resultssupporting
confidence: 88%
“…All the analyzed variables, except for survival, showed significant differences (P<0.05). Vieira et al (2008) found similar results to the meal evaluated in the present study for dry matter (92.2%), crude protein (3.9%), crude fiber (14.6%), ether extract (4.4%) and mineral matter (2.1%). However, they found different values for crude fiber, due to the inclusion of the mango seed and skin, which might have affected the nutritional values.…”
Section: Resultssupporting
confidence: 87%
“…Melo et al (2012), avaliaram a inclusão de farinha de manga sem cascas substituindo o milho, concluíram que a substituição de 100 % do milho por manga não prejudica o desempenho. O farelo de resíduo de manga uma fonte alternativa, possui baixos teores de lipídios, minerais e proteínas (Vieira et al, 2008), entretanto possui valores energéticos de 3724 kcal/kg de ração (Lima et al, 2011) bem próxima à energia contida no milho (3886 kcal/kg de ração) em rações para peixes (Oliveira Filho e Fracalossi, 2006). Como pode ser observado na (tabela I), as rações com maiores concentrações de energia foram as que continham farinha de manga.…”
Section: Resultsunclassified